A parametric strength study of jarosite waste. Issue 1 (21st February 2018) - Gupta, Chayan; Prasad, Arun
Abstract : A parametric study that controls the compressive and tensile strengths of artificially cemented jarosite has been made. The present work advocates the leverage of lime ( L ), ground granulated blast-furnace slag (GGBS) ( G ) and curing period ( t ) in quantifying the unconfined compressive strength ( q u ) and split tensile strength ( q t ) of artificially cemented jarosite. A number of strength tests are carried out on jarosite stabilised with various contents of lime (2·5–10%) and GGBS (10–40%). The results show that both, q u and q t increase non-linearly with the increase in lime and GGBS content. A power function has been fitted to assess the best relationship between q t / q u and L, t and G . Finally, a unique relationship between q t and q u is established – that is q t / q u, being independent of all the above-listed parameters. The microstructural study also shows the presence of larger agglomeration of particles on addition of GGBS and lime, implying an increase in strength of stabilised jarosite waste.